Double Intuitionistic Continuous Function in Double Intuitionistic Topological Spaces - Asmaa Ghassob Raoof; Taha H. Jassim (Tikrit Journal of Pure Science)
The aim of this paper is to introduce a new classis of Double intuitionistic continuous function, Double intuitionistic (open and closed) functions in Double intuitionistic topological spaces, we investigate the properties of the relationships among these types.